Perspektif Hukum Islam terhadap Budaya Mangupa - Nurfitryani Siregar; Linamayasari Siregar; Irmasuryani Siregar (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
Mangupa is a traditional ritual that is still preserved by the people of South Tapanuli as a form of gratitude to Allah SWT for success or avoidance of danger. This tradition also aims to return the tondi (soul/spirit) to the body so that a person can return to health. In the Mangupa procession, food is served and "hata pasu-pasu," which is an expression of prayer, advice and hope conveyed by family and traditional leaders. This procession is held at certain moments such as sirian (joy) and siluluton (sorrow), and uses traditional materials that have been determined. This research is descriptive analytical in nature which aims to explain the view of Islamic law regarding the implementation of Mangupa. Through a qualitative approach, the author tries to understand how this ritual is practiced in people's lives and how Islamic law views this tradition. From the research results, the implementation of Mangupa in Paringgonan Village was declared permissible (allowed) as long as it did not contain elements of shirk, superstition, lies or excessive waste. If in the future Mangupa violates religious principles, such as destroying beliefs or causing waste, his legal status could change to makruh or haram. The essence of Mangupa is an expression of gratitude, prayer and advice, which is in accordance with Islamic teachings, so that its practice is still acceptable as long as it does not conflict with the Shari'a.